Revisiting Article 33(3) of the Constitution of the Republic of Indonesia Through the Perspective of Law and Economics - Lewiandy Lewiandy; Janice Arivi Puji; Natania Kayla Tanujaya (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This paper explores the connection between Article 33(3) of the 1945 Constitution of Indonesia, the welfare state theory, and the Kaldor-Hicks efficiency principle in the management of natural resources, particularly in the oil and gas sectors, using a normative juridical method. Since independence, Indonesia has been founded on the rule of law, ensuring justice, equality, and protection for its citizens. Article 33(3) establishes the philosophical and economic foundation of Indonesia’s welfare state by mandating that vital sectors and natural resources be controlled by the state for the people’s prosperity. However, globalization and excessive state monopolization have created inefficiency, corruption, and slow growth. Integrating the welfare state theory, which emphasizes public welfare, with the Kaldor-Hicks principle, which values policies that increase overall societal well-being even if some are disadvantaged, provides a more balanced framework. Allowing private participation under strict state supervision can enhance efficiency and innovation while maintaining constitutional integrity. The term “state control” should be understood as a regulatory and supervisory function rather than absolute ownership, ensuring accountability, transparency, and fairness. Thus, effective governance requires the state to act as both facilitator and regulator, balancing social justice and economic efficiency. This combination of welfare and efficiency theories, analyzed through a normative juridical approach, supports a constitutional model that promotes equitable and sustainable national prosperity.